2019
DOI: 10.1016/j.ultsonch.2019.104708
|View full text |Cite
|
Sign up to set email alerts
|

Collective nonlinear behavior of interacting polydisperse microbubble clusters

Abstract: Exploiting the full potential of MBs for applications requires a good understanding of their complex dynamics. Improved understanding of MB oscillations can lead to further enhancement in optimizing their efficacy in many applications and also invent new ones. Previous studies have predominantly addressed the behavior of a single isolated MB in an infinite liquid domain, whereas most applications employ MBs in clusters. Oscillating MBs have been shown to generate secondary pressure waves that modify the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 89 publications
2
37
0
Order By: Relevance
“…Effects of coupling, bubble size, and spatial arrangement have been studied in [102] and effects of boundary proximity on the dynamics of a bubble cluster is investigated in [103] . We have shown in [105] that the bubble cluster may exhibit collective behavior dominated by the response of the larger bubbles. Future studies need to look into the effect of the interaction of lipid coated MBs and potential collective behavior of the lipid coated bubbles at lower excitation pressure amplitudes.…”
Section: Limitations and Future Workmentioning
confidence: 94%
See 1 more Smart Citation
“…Effects of coupling, bubble size, and spatial arrangement have been studied in [102] and effects of boundary proximity on the dynamics of a bubble cluster is investigated in [103] . We have shown in [105] that the bubble cluster may exhibit collective behavior dominated by the response of the larger bubbles. Future studies need to look into the effect of the interaction of lipid coated MBs and potential collective behavior of the lipid coated bubbles at lower excitation pressure amplitudes.…”
Section: Limitations and Future Workmentioning
confidence: 94%
“…Bubble–bubble interaction should also be considered as in applications bubbles exist in poly-disperse clouds. The bifurcation structure of the interacting bubbles has been studied extensively in [99] , [100] , [101] , [102] , [103] , [104] , [105] . These studies have shown that the bubble–bubble interaction significantly influences the dynamics of each bubble.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…However, non-spherical oscillations, especially in larger bubbles can significantly influence the bubble behavior [4,63,64,65] and threshold of SH emissions [31,32]. Bubble-bubble interaction is another important factor that changes the threshold of SH emissions in mono-disperse bubble clouds [40] as well as poly-disperse bubble clouds [66,67,68]. Interaction with a boundary also influences the pressure threshold of SH emissions [68].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…to describe the cavitation bubble dynamics in soft tissues and to analyze the resultant acoustic emissions, but only focusing on a single bubble for simplicity [24] , [25] , [26] , [27] . For the bubble–bubble interactions, many researches have been focused on the translational motions or radial pulsations of bubbles in Newtonian fluids [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] . It has demonstrated that the bubble–bubble interactions make them behave very differently from individual bubbles.…”
Section: Introductionmentioning
confidence: 99%